Small Donors in Congressional Elections. Issue 5 (September 2019) - Culberson, Tyler; McDonald, Michael P.; Robbins, Suzanne M.
Candidates raise substantial sums of money to compete in federal elections. Scholars and election observers are concerned by potential corruption related to the reliance on donors who make significant contributions. One reform effort to counterbalance large donors is encouraging small donor participation. Still, some worry that ideologically extreme candidates are best able to raise small donations. We analyze internal U.S. Federal Elections Commission data to examine small donor giving in the 2006 through 2010 U.S. House elections. We find small donors may expand the scope of participation, in that the supply of small donors is unrelated to income and that all types of candidates—incumbents, their challengers, and open seat candidates—are equally adept at attracting small donors. Candidates in the most competitive races raise the most in small contributions. We temper reformers' enthusiasm, finding that ideologically extreme incumbents tend to raise more money from small donors.